2013
DOI: 10.1017/s0033291713001815
|View full text |Cite
|
Sign up to set email alerts
|

Altered reward processing in the orbitofrontal cortex and hippocampus in healthy first-degree relatives of patients with depression

Abstract: Our study in first-degree relatives of depressive patients showed abnormal brain responses to aversive and rewarding outcomes in regions known to be dysfunctional in depression. We further confirmed the reversal of these aberrant activations with SSRI intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
3
32
1
Order By: Relevance
“…In addition, studies investigating the effects of SSRI treatment reported a decrease of frontocortical hyperactivation or hypermetabolism in patients with OCD 15,39 and their healthy siblings. 40 In line with these findings, our finding of SGA-dependent differential activation in the OFC suggests opposite effects of SSRIs and SGAs with pronounced antiserotonergic properties.…”
Section: Differential Sga Effects On Brain Activationsupporting
confidence: 85%
“…In addition, studies investigating the effects of SSRI treatment reported a decrease of frontocortical hyperactivation or hypermetabolism in patients with OCD 15,39 and their healthy siblings. 40 In line with these findings, our finding of SGA-dependent differential activation in the OFC suggests opposite effects of SSRIs and SGAs with pronounced antiserotonergic properties.…”
Section: Differential Sga Effects On Brain Activationsupporting
confidence: 85%
“…41 Furthermore, our findings are well in line with research showing hyperactivation of the medial prefrontal cortex during sad mood induction as a feature of relapse risk in individuals with remitted depression. 42 On the other hand, altered functioning of the OFC has been shown during reward processing in firstdegree relatives of patients with MDD. 43 However, these findings must not be regarded as contradictive to the present results; rather, they refer to the complex role of the OFC in different conditions in terms of diverging signalling during different paradigms, such as emotional face matching or reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, depression and psychosis frequently co-occur and there are a number of ways in which motivational and hedonic impairments operate similarly in psychosis and mood pathology. For example, motivational/hedonic impairments can be present in individuals at risk for developing psychosis (Delawalla et al 2006;Glatt et al 2006;Juckel et al 2012;Grimm et al 2014;Schlosser et al 2014) or at risk for developing depression (Gotlib et al 2010;Foti et al 2011a, b, c;McCabe et al 2012;Kujawa et al 2014;Macoveanu et al 2014;Olino et al 2014;Sharp et al 2014). Further, there is evidence that the presence or severity of motivational/hedonic impairments is associated with the development of manifest illness for both psychosis (Chapman et al 1994;Kwapil et al 1997;Gooding et al 2005;Velthorst et al 2009) and depression (Bress et al 2013;Morgan et al 2013).…”
Section: Introductionmentioning
confidence: 99%